Expectations and Perceptions in Developing Countries: Their Measurement and Their Use - Attanasio, Orazio P (American Economic Review, 2009)
The use of microeconomic data has become extremely widespread in applied economics. Household and firm level data are now routinely used not only in labour and industrial organization, but also in macroeconomics. The use that is made of the data is extremely varied, ranging from simple comparison of means in the evaluation literature based on Randomized Control Trials, to the matching of some data moments to calibrate the structural parameters of complex models of individual behaviour to the structural estimation of dynamic optimization models. At the same time, partly as consequences of technology advances, many more data sets are available. And much more detailed and high quality data are being collected. From a methodological point of view, important advances have been made in the techniques aimed at the elicitation in surveys of information about a variety of factors that constitute important inputs in the empirical analysis of economic behaviour. A good example, for instance, is the collection of information on household financial and non financial wealth, which was thought to be a very difficult if not impossible variable to measure accurately in a household survey and, instead, is now collected routinely and satisfactorily in many surveys, thanks to the development and standardization of new